Acute appendiceal abscess and atraumatic splenic rupture: A case of dual pathology. (2016) - Ananthavarathan, Piriyankan; Patel, Kamlesh; Doran, Catherine; Suggett, Nigel
Highlights: Acute appendicitis may co-present with atraumatic splenic rupture. Hypovolaemic shock secondary to splenic rupture may co-exist with septic shock. Complex presentations warrant careful consideration and swift management of dual pathologies. Abstract: Introduction: Atraumatic splenic rupture is a rare surgical emergency that is often attributed to neoplastic or infectious causes. Rarely, it has been identified to also occur in the setting of an acute severe sepsis and in cases of pelvic or splenic abscess formation post-appendicectomy. However, to our knowledge, the co-presentation of acute appendiceal abscess and splenic rupture has not been previously described. Presentation of case: We present the case of a 67-year old male with decompensating haemorrhagic shock secondary to atraumatic splenic rupture on a background of an inadequately treated complicated appendicitis originally managed as diverticulitis with antibiotics in the community. Intra-operatively, in addition to a de-gloved, ruptured spleen; an acutely inflamed appendiceal abscess was also identified. A concomitant splenectomy, washout and appendicectomy and was therefore performed. Histopathological examination revealed a normal spleen with a stripped capsular layer. Mucosal ulceration, transmural inflammation and serositis of the appendix appeared to be consistent with acute appendicitis. Discussion: Our case demonstrates how inadequately treated sepsis may predispose to an acute presentation of splenic rupture with associated haemorrhagic shock; which may initially be interpreted as septic shock. However, we demonstrate how insults such as sepsis and haemorrhagic shock may co-exist warranting careful consideration of possible dual pathologies in complex presentations which may be life-threatening. Conclusion: While the causal relationship between acute appendicitis and atraumatic spontaneous splenic rupture remains unclear, our case considers and highlights the importance of considering dual pathology in patients presenting in the acute setting.